Seamless Automation: Integrating BPM and RPA with Pega - Munnangi, Sivasatyanarayanareddy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The integration of Business Process Management (BPM) and Robotic Process Automation (RPA) within the Pega platform provides a transformative approach to process automation. BPM enables the orchestration of complex workflows and case management, while RPA automates repetitive tasks, driving efficiency across various business functions. Pega’s unified platform integrates these capabilities with AI-driven decision-making, intelligent case management, and adaptable automation, allowing seamless collaboration between human workers and robotic agents. This article explores the technical architecture, integration strategies, and best practices for combining BPM and RPA within the Pega ecosystem. Supported by real-world case studies, it demonstrates how this synergy enhances operational excellence, reduces costs, ensures compliance, and accelerates digital transformation in diverse industries. Through a detailed exploration of implementation steps and key challenges, businesses can uncover how this powerful integration transforms workflows to deliver sustainable results.